Princess in disguise - Baker, E. D. (New York : Bloomsbury, 2015)
When everything starts going wrong on Annie and Liam's wedding day, Queen Karolina decides that they need the help of her fairy godmother, Moonbeam, but a magical fog keeps messengers from leaving so Annie and Liam themselves set out to discover who ruined the wedding, and why.
5.5
5-8
790L
Keywords: Princesses -- Juvenile fiction; Magic -- Juvenile fiction; Disguise -- Juvenile fiction; Weddings -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Princesses -- Fiction; Magic -- Fiction; Disguise -- Fiction; Weddings -- Fiction; Characters in literature -- Fiction; Fairy tales; Princesses -- Fiction; Magic -- Fiction; Disguise -- Fiction; Weddings -- Fiction; Characters and characteristics in literature -- Fiction; Fairy tales; JUVENILE FICTION / Fairy Tales & Folklore / General; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Love & Romance; Fairy tales; Princesses -- Fiction; Magic -- Fiction; Disguise -- Fiction; Weddings -- Fiction; Characters in literature -- Fiction; Fairy tales